Colloidal synthesis and characterization of single-crystalline Sb2Se3 nanowires. Issue 40 (5th May 2017) - Liu, Yike; Tang, Yaqin; Zeng, Ying; Luo, Xun; Ran, Jingyu; Luo, Yongmei; Su, Xiangdong; Ng, Boon K.; Liu, Fangyang; Jiang, Liangxing
Abstract : Single-crystalline Sb2 Se3 nanowires have been synthesized by a hot-injection phosphine-free colloidal method and show excellent photoelectrochemical properties. Abstract : In the present study, single-crystalline Sb2 Se3 nanowires have been synthesized by a hot-injection method. The crystal structure of the prepared Sb2 Se3 nanowires has been comprehensively characterized by a series of techniques, namely X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM) as well as selected area electron diffraction (SAED). The mechanism of formation of amorphous phase and nanowires has also been intensively investigated. It is evident that the formation of Sb2 Se3 nanowires strongly depends on the reaction temperature. A band gap of 1.06 eV for Sb2 Se3 nanowires has been ascertained from UV-vis-NIR measurements. Moreover, coated film consisting of Sb2 Se3 nanowires demonstrates a clear photoresponse in photoelectrochemical measurements. This work has conclusively demonstrated that Sb2 Se3 nanowires have great potential in solar energy conversion.